A Case of Recurrent Acute Pain Transfusion Reactions Due to Platelet Transfusion. (28th October 2020) - Robertson-Patera, J; Lu, W
Abstract: Introduction/Objective: Transfusion of blood components is one of the most common medical procedures with transfusion reactions being the greatest associated risk. Acute pain transfusion reaction (APTR) is one such under- recognized and under-reported risk, likely due to scarcity of literature and lack of criteria for diagnosis. Methods: A literature review was performed using PubMed to search for the keywords: "acute pain transfusion reaction". This searched revealed two articles, from which one abstract and a book chapter were also identified. Results: A 58-year-old female with chronic myeloid leukemia and pre-existing pain received 44 leukoreduced irradiated blood components [7 pooled platelets, 17 apheresis platelets, 20 red blood cells (RBCs)] over two months. Four platelet (one pooled, three apheresis) transfusions resulted in chest and lower back pain starting an average of 15 minutes after initiation of transfusion and resolving following cessation of transfusion. Laboratory evaluations were negative for hemolysis. Despite the patient's history of pain, these reactions were most consistent with APTRs. APTRs are rare, most often associated with leukoreduced RBCs and characterized by severe pain in the abdomen, back, flank, or proximal extremities typically occurring within 30 minutes of starting transfusion and abating within 30 minutes following cessation of transfusion. All of our patient's reported reactions occurred in association with leukoreduced platelets. These reactions may be associated with the leukoreduction, but reports of APTR appeared when leukoreduction became standard practice. Therefore, the etiology remains unknown. Conclusion: This case aids in the argument that APTR is a complication of transfusion, despite the absence of a clear etiology or diagnostic criteria. Additional research and improved surveillance are necessary to elucidate potential etiology and improve patient care by identifying prevention and treatment options. A diagnostic criterion would aid efforts to harmonize reporting in the United States and collect the hemovigilance data required to improve transfusion outcomes.